Multilocation Evaluation for yield and Yield Related Traits in Three-Way Cross Maize Hybrids in Kenya - Masila, Benard; Langat, Charles (International Journal of Scientific Research in Biological Sciences, 2020)
Maize (Zea mays L.) is the third most important crop after wheat and rice worldwide. It is the main staple food in Kenya. The objective of this study was to evaluate genotype by environment interactions and yield stability of twenty three-way cross hybrids at four locations in Kenya evaluated in two seasons. The experiment was conducted in an alpha lattice design (Incomplete Randomized Block Design) with three replications. There was significant variation for grain yield among the genotypes, locations and their interaction. Stability analysis was evaluated using the joint regression, additive main effects and multiplicative interactions (AMMI) and GGE biplot methods. The environmental and genotypic means ranged from 2.72 to 7.67 and 2.39 to 5.56 respectively. The regression coefficient (βi) and deviation from regression (s2di) values of these genotypes ranged from 0.55 to 1.64 and 0.02 to 0.59 respectively. There were also significant differences for genotypes, environments and genotype by environment interaction for the AMMI analysis of variance. The total proportion of variation contributed by genotypes, environments and genotype by environment interaction was 8.82%, 76.03% and 9.17% respectively. When considering the Pi, βi, S2 di and the AMMI biplot analysis, the most stable genotype in the high yielding category in this study considering all stability parameters was WE-CMT-TWC-1001 (G1) followed by WE-CMT-TWC-1003 (G3) and WE-CMT-TWC-1020 (G20). The best genotype with both high mean yield and high stability was WE-CMT-TWC-1003 (G3). The genotypes identified could be utilized as reference for genotype evaluation and tested further for selection.